Analisis Sistem Penurunan Konsolidasi Multi-Layer - Rofika Ratna Ardiansyah; Syawal Satibi; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Construction on thick soft soils is often faced by settlement problems, which need particular concern. In order to reduce settlement friction piles are often used. However the effectiveness of group friction piles related to their dimension has not been fully understood. Therefore settlement analysis need to be conducted. In addition, in practice one-point settlement is generally used for preliminary assignment. This approach is considered to be very rough analysis. This research will show the comparison between one-point method and multi-layer method. For group friction pile analysis, simplified boussinesq stress distribution (2 verticals : 1 horizontal stress distribution) is applied in settlement calculation. This research shows that multi-layer settlement calculation is recommended for preliminary settlement assignment. Keywords: friction pile, settlement, multi-layer, stress distribution